2022
DOI: 10.3390/diagnostics12071574
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Uterine Rupture and Adenomyosis, a Rare but Possible Correlation: Case Report and Literature Review

Abstract: (1) Background: Uterine rupture during pregnancy is a serious obstetric complication with a high incidence of maternal morbidity and mortality. (2) Methods: The present case is a rare event of a uterine rupture occurring in an unscarred uterus in a nonlaboring primigravida woman in the second trimester. The only risk factor in this case was adenomyosis found in the preconceptional phase. (3) Results: The diagnosis of adenomyosis can often be difficult, so patients should be evaluated by a specialized gynecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Although there are many studies related to uterine rupture [ 9 , 10 ] and pelvic floor dysfunction due to pregnancy and delivery in the clinic, we could not find any study in the literature that histologically demonstrated the effect of oxytocin hormone on pelvic floor muscles. To our knowledge, this is the first study in the literature demonstrating the effects of oxytocin induction on pelvic floor muscle in rats.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Although there are many studies related to uterine rupture [ 9 , 10 ] and pelvic floor dysfunction due to pregnancy and delivery in the clinic, we could not find any study in the literature that histologically demonstrated the effect of oxytocin hormone on pelvic floor muscles. To our knowledge, this is the first study in the literature demonstrating the effects of oxytocin induction on pelvic floor muscle in rats.…”
Section: Discussionmentioning
confidence: 76%
“…Pregnancy and childbirth are common risk factors for complications such as placenta previa, uterine rupture, preeclampsia and pelvic floor disorders (PFDs) [ 8 , 9 , 10 ]. The symptoms of PFDs include urinary incontinence, bladder storage and voiding and post-micturition, pelvic organ prolapse, sexual dysfunction, anorectal dysfunction, lower urinary tract pain and/or other pelvic pain and lower urinary tract infections [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effort was due first of all to the impossibility of knowing how to manage a pandemic with the health complications that have arisen and, secondly, to the absence of targeted COVID-19 drugs, which in the first pandemic phase saw the experimentation of therapies already existing for others purposes and, in principle, were at least adaptable to the pulmonary and systemic symptoms presented by patients COVID-19 affected [ 155 , 156 , 157 , 158 , 159 , 160 ]. The advent of vaccines [ 85 , 161 , 162 , 163 ] has in fact revolutionized this perspective as they have guaranteed not only a preventive and protective effect in the contagion phase, but also a therapeutic effect as severe symptoms have increasingly given way to milder symptoms or even a lack of symptoms in the vaccinated population. This aspect must also be taken into consideration for extra-pulmonary symptoms, even in the long-term, assuming future viral variants and future vaccines.…”
Section: Discussion and Potential Future Approachesmentioning
confidence: 99%
“…Labor analgesia is reported to be the most effective technique for pain control during labor [ 16 , 50 , 51 ]. Bofill, in 1996, compared the effectiveness of forceps and VE in terms of the need for analgesia during labor.…”
Section: Operative Vaginal Delivery: Forceps and Vacuummentioning
confidence: 99%